Marketing-based human resource management strategy development - Pashchuk, Lidiia (Technology audit and production reserves, 2016)
Chemical sector of Ukraine today operates in quite difficult conditions caused by economic, structural, institutional, market, technological changes and serious risks, which recently added. Due to economic downturn the enterprises of this sector faced with some significant human resource management problems such as negative outflow of qualified employees, problems with attraction of young specialists and retention of the existing employees. Ukrainian citizens don’t limit their job search with local employer but also they are ready to look for foreign employment opportunities. That is why it is crucially important to launch progressive and effective human resource management approaches in order to improve current situation at Ukrainian chemical sector employers. In the article the methodical approach to developing HR strategies based on marketing was offered as well as an assessment of companies using the proposed method was conducted. Methodical approach stipulates logical steps of managerial actions in order to assess the current state of human resource management within the company and develop an effective human resource strategy later. According to the developed tools, the overall assessment of the human resources management in the chemical industry enterprises of Ukraine was fulfilled. Based on the results of the analysis it was defined that the current state of the human resource management in researched companies significantly varies. Research investigations enabled to form recommendations regarding human resource management strategy formation for the enterprises with different needs.